Design of Leakage Gas Induction Channels for Reliable Planar-Type Solid Oxide Fuel Cell Stacks. (30th May 2017) - Yoon, Heesung; Jang, Inyoung; Kim, Chanho; Kim, Sungmin; Paik, Ungyu
Abstract : The leakage of gas in a planar solid oxide fuel cell (SOFC) stack is one of the important factors associated with stack degradation. When the fuel leaks to the air electrode, the catalytic property of the cathode deteriorates. Further, when air leaks to the anode comprised of Ni metal, the electrolyte thin film is peeled from the anode surface as result of the re-oxidation of Ni. Therefore, one of the ways to prevent these deterioration characteristics of the SOFC stack is to design a sealing method that can prevent gas leakage. In this study, we have developed a stack with specially designed channels which incorporates sealing gaskets that release leaked gas to outside, thereby preventing it from flowing into the fuel and air electrodes and ensuring the stability of the SOFC stack. The stack is designed to function with 10x10 cm 2 size cells, and to undergo frequent thermal cycles rising from room temperature to operation temperature and then back to room temperature.